STUDYING THE SOCIAL, EDUCATIONAL AND EDUCATIONAL SIGNIFICANCE OF SCIENTIFIC AND POPULAR ARTICLES IN PRIMARY SCHOOL TEXTBOOKS - Hasanova Gulbahor Davlatmamatovna; Muminova Umida Karshievna (Zeta Repository, 2023)
This article shows that it is necessary to provide primary school students with certain knowledge about nature, people's work and social life, to teach children to work independently with books and to gain specific knowledge from them, as well as refer to history, study modern , it was mentioned that the modern organization of education is of great importance in getting acquainted with the life of great people, and in addition, in studying all scientific and popular articles.